The budget impact of alteplase in the treatment of acute ischemic stroke in Egypt - Aref, Hany; El Nahas, Nevine; Elsisi, Gihan Hamdy; Shokri, Hossam; Roushdy, Tamer (Frontiers in Neurology, 2023)
Introduction Stroke is the second leading cause of mortality worldwide. Five percent of all the disability-adjusted life years (DALYs) lost around the world are attributed to stroke. This study aimed to assess the economic burden of acute ischemic stroke (AIS) in Egypt and reveal the benefits of alteplase treatment by measuring the resource use and costs associated with this treatment compared to the standard of care and extrapolate the overall budget impact of alteplase to the local Egyptian setting over a 5-year time horizon from a societal perspective. Methods A budget impact model was developed to estimate the impact of adding alteplase to the current treatment of AIS patients within the Egyptian healthcare setting. The efficacy data for both arms of the model were sourced from a systematic review of the literature. Resource use and cost data were sourced from a retrospective study. Proportions of patients potentially eligible for treatment and the treatment time distributions were estimated from an analysis of the results of this retrospective data collection. A univariate sensitivity analysis was conducted to assess the robustness of the model results. The input parameters varied between plausible extremes based on a review of available evidence. Results The total annual costs with alteplase treatment [i.e., drug, symptomatic intracerebral hemorrhage (ICH) management, acute hospitalization, and post-hospitalization costs] for the targeted patients from a societal perspective were estimated to be less than the total annual costs without alteplase. This resulted in savings of approximately EGP 37.2 million ( 1.2 million), EGP 14.2 million ( 458.06), EGP −33.0 million ( −1.06 million), EGP −54.0 million ( −1.74 million), and EGP −89.8 million ( −2.89 million) for each of the 5 years, respectively. In year 1, more than 2,787 patients (+30.1%) achieved an excellent outcome and <1,204 patients (−22.3%) had a poor outcome when treated with alteplase. The savings in acute hospitalization and post-hospitalization costs offset the increase in drug and ICH management costs in the alteplase group compared to treatment without alteplase. The total cumulative cost savings for alteplase in AIS patients were estimated at EGP −228,146,871 ( −7,359,576) over 5 years. Conclusion The budget impact model estimates suggest that from a societal perspective, alteplase is likely to be a cost-saving option for the treatment of AIS in Egypt due to the treatment benefits, resulting in savings in acute hospitalization and annual post-hospitalization costs.